RESPONSE OF RED GINGER TO APPLICATION OF BIOFERTILIZER AND ROCK PHOSPHATE UNDER DIFFERENT AGROECOLOGICAL CONDITIONS - Muchamad Yusron (Pusat Penelitian dan Pengembangan Perkebunan, 2009)
In relation to the safety and efficacy of herbal medicinal plants, World Health Organization (WHO) has stated that each natural herbal production must be cultivated with good agricultural practices (GAP). There-fore, Indonesia is trying to develop regional and national guidelines for good agricultural practices, including organic farming. The objective of this experiment was to provide technical support for the GAP development to ensure product safety of raw material of medi-cinal herbal industry, especially on fertilization technique. The research was conducted at Cibinong (Bogor) and Sukamulia (Sukabumi) experimental stations from October 2005 to August 2006. Three promising lines of red ginger were planted, i.e. Balittro1, Balittro2, and Balittro3. The fertilizers applied were 10 ton compost + 90 kg bio fertilizer + 300 kg Zeolite + 300 kg rock phosphate per hectare. Results showed that fresh rhizome yield of red ginger depended on local conditions. Rhizome yields of red ginger cultivated in Sukamulia were 6.33; 5.91; and 7.31 t/ha for Balittro1, Balittro2, and Balittro3, respectively. These yields were higher than those cultivated in Cibinong, which were 3.82; 4.38; and 4.48 t/ha. The symplicia quality based on ginge-rols content and water soluble extract content, of red ginger cultivated in Cibinong produced better quality than that cultivated in Sukamulia.